Comparing Self-esteem and Self-concept of Athletic and Non-Athletic Students and Finding a Relationship between these two Variables - Seyedeh Khadijeh Asady; Zahra Tasaddoghi; Mohadeseh Tavakoli (The Society of Aging and Physical Activity (SAPA), 2013)
This study aims to compare and determine a relationship between self-concept and self-esteem of female and male athletic and non-athletic students in Sari branch Islamic Azad University. For this reason, 200 students (100 athletic and 100 non-athletic) were selected randomly and tested by Eysenck's self-esteem questionnaire and Rogers's self-concept one. Research findings implied that there is no significant relationship between self-esteem of athletic students and non-athletic ones. However, there is a significant relationship between self-esteem of female non-athletic students and male non-athletic ones.